Senicapoc treatment in COVID‐19 patients with severe respiratory insufficiency—A randomized, open‐label, phase II trial. Issue 7 (13th May 2022) - Granfeldt, Asger; Andersen, Lars W.; Vallentin, Mikael F.; Hilberg, Ole; Hasselstrøm, Jørgen B.; Sørensen, Lambert K.; Mogensen, Susie; Christensen, Steffen; Grejs, Anders M.; Rasmussen, Bodil S.; Kristiansen, Klaus T.; Strøm, Thomas; et al.
Abstract: Background: The aim of the current study was to determine if treatment with senicapoc, improves the PaO2 /FiO2 ratio in patients with COVID‐19 and severe respiratory insufficiency. Methods: Investigator‐initiated, randomized, open‐label, phase II trial in four intensive care units (ICU) in Denmark. We included patients aged ≥18 years and admitted to an ICU with severe respiratory insufficiency due to COVID‐19. The intervention consisted of 50 mg enteral senicapoc administered as soon as possible after randomization and again after 24 h. Patients in the control group received standard care only. The primary outcome was the PaO2 /FiO2 ratio at 72 h. Results: Twenty patients were randomized to senicapoc and 26 patients to standard care. Important differences existed in patient characteristics at baseline, including more patients being on non‐invasive/invasive ventilation in the control group (54% vs. 35%). The median senicapoc concentration at 72 h was 62.1 ng/ml (IQR 46.7–71.2). The primary outcome, PaO2 /FiO2 ratio at 72 h, was significantly lower in the senicapoc group (mean 19.5 kPa, SD 6.6) than in the control group (mean 24.4 kPa, SD 9.2) (mean difference −5.1 kPa [95% CI −10.2, −0.04] p  = .05). The 28‐day mortality in the senicapoc group was 2/20 (10%) compared with 6/26 (23%) in the control group (OR 0.36 95% CI 0.06–2.07, p  = .26). Conclusions: Treatment with senicapoc resulted in a significantly lower PaO2 /FiO2 ratio at 72 h with no differences for other outcomes.